Art toy as a tool for engaging the global public on the city of Surabaya. Issue 2 (4th May 2022) - Kuntjara, Aristarchus Pranayama
Abstract: Art toys, often called designer toys, are three-dimensional figures of hybrid and stylised characters that are reproduced and commonly customised in limited quantities and sold among segmented hobbyists and collectors. Within this niche, however, there is an unexplored territory of art toy character design that is based on a city's symbols. Such is the case with the city emblem of Surabaya, Indonesia, which already has the iconic images of a shark and a crocodile ( Suro and Boyo ). As Surabaya continuously focuses on its image, art toys based on the city's symbols prove to be a potential platform and asset for engaging the public towards the city. If aligned and integrated well with tourism activities, licensing, branding, and various marketing communication media, it is a prospective resource and intellectual property for the city's public diplomacy in local and global settings. This article traces and conveys the design process and investigates the possibilities and concerns of designing and promoting an art toy platform character named Subo, based on Surabaya's city symbol.